The diachronic Malaysian English corpus (DMEC) : design, development and challenges - Hajar Abdul Rahim; Raihana Abu Hasan; Ang, Leng Hong; Siti Aeisha Joharry (Penerbit Universiti Kebangsaan Malaysia, 2021)
Malaysian English (ME) has received much research attention in terms of its linguistic system, and use. In the last two decades, with the development of language corpora and corpus methods, research in ME as an Outer Circle and postcolonial variety increased significantly. These corpus-based studies are important and indeed interesting but they are limited to descriptions and discussions on contemporary ME, as they are based on synchronic ME corpora. Research in diachronic changes in ME, to date, is rare to say the least. To address this gap and facilitate systematic examination of changes in ME necessitates the development of diachronic ME corpora. This article reports on the design and development of the first diachronic Malaysian English corpus (DMEC), comprising Malaysian English written texts from the 1960s until the 2010s. The six decades represent three phases of English in Malaysia, end of colonial era, postcolonial and contemporary ME. The corpus is designed to facilitate research in ME changes in terms of its linguistic system, identity and trajectory. Besides the design and development of the DMEC, three sample analyses based on the existing corpus are discussed to demonstrate the value of the corpus as a resource for diachronic research in ME. The current article, overall, contributes to existing knowledge on the development of language corpora in Malaysia and foregrounds the potential of diachronic research in ME.